Physical activity on prescription (PAP) as a resource of treatment in Iceland: General practitioners’ view - Laufey Ásta Guðmundsdóttir 1989- (2015)
The aim of the research was to examine Icelandic general practitioners’ (GPs) attitude towards physical activity on prescription (PAP), as well as finding ways to improve and increase the use of the resource of treatment in Iceland. Physical activity has proved effective as a treatment for and in prevention of many health problems. PAP is a resource of treatment to increase a patient’s physical activity level when appropriate. The study is both qualitative and quantitative. A questionnaire was sent to 239 e-mail addresses from a post list obtained from The Association of Icelandic General Practitioners. 93 GPs participated, while 92 were valid. Out of the six GPs who were contacted, five participated in interviews. The interviews were between 15-20 minutes in length and the interviewer used an interview frame for guidance throughout the interviews. Results indicate that GPs’ attitudes towards PAP were more positive than expected. The attitude did not differ from the GPs’ gender or employment age but a low significant correlation was found between attitude and the GPs’ physical activity level. Prescriptions of PAP in Iceland could be increased with more public knowledge about it, to increase awareness, and by constantly reminding the GPs about it so the usage of PAP eventually becomes a part of their routine. Keywords: Physical activity on prescription (PAP), general practitioner (GP), attitude, lifestyle illnesses, health promotion. Markmið rannsóknarinnar var að kanna viðhorf Íslenskra heimilislækna til hreyfingar samkvæmt lyfseðli sem nefnist Hreyfiseðill, auk þess að leita leiða til að bæta og auka notkun úrræðisins hér á landi. Hreyfing hefur reynst áhrifamikil meðferð og fyrirbyggjandi fyrir ýmis heilsuvandamála. Rannsóknin er bæði eigindleg og meigindleg. Spurningalisti var sendur á 239 tölvupóstföng á póstlista Félags íslenskra heimilislækna (FÍH) og 93 svöruðu könnuninni, en 92 svör reyndust gild. Fimm af sex heimilislæknum, sem boðið var til viðtals, samþykktu þátttöku í eigindlega hluta ...